CASE ON EDUCATIONAL STANDARDS - Oleg A. Donskikh (Высшее образование в России)
In the article the situation in the Russian higher education system is analyzed in relation to the incessant transition from one set of standards to another, and this has been going on for 15 years, since the adoption of the standards of the first generation. It is shown that the requirement of actualizing of the educational standards in order to match the professional standards can bring only a huge additional workload that will impact on the educational process itself only negatively. In particular, it is called to question the practicability of putting into action the standards of the generation 3+ in conditions when it is known for their shortcomings. The author draws attention to the negative effects of the total subordination of higher education to the badly formulated economic needs at the expense of other purposes, including cultural development of personality and its self-identification. It is noted that the reforms in the total absence of academic freedom set free higher school lecturers from any responsibility for the result of education, and this is bad either for themselves or for the system as a whole. The author defends the point of view that standardization of education oriented onto purely economic aspect of life cannot lead to any positive result in principle. This is evidenced by the experience of other countries.